(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article migration position in Republic Kazakhstan and as illegal migration in territory is considered. Development of migration in the Republic of Kazakhstan increases illegal migration and including human rights are broken. The author offers ways of the decision of these problems as analyzes legislative system of country.